Humidity-dependent characteristics of DNA thin film-based Al/DNA/Al surface-type cell - Al-Ta'ii, H.M.J.; Periasamy, V.; Amin, Y.M. (Elsevier, 2016)
We describe the experimental results for humidity-dependent capacitive response of semiconducting DNA thin films incorporated into Aluminum (Al)/DNA/Al surface-type Schottky diode. The DNA film was deposited using drop-casting method onto a glass substrate pre-deposited with Al followed by an Al contact to fabricate the Al/DNA/Al Schottky junctions. Alpha radiation irradiation was then carried-out for different periods (10, 20, 30 and 40 min). Results indicate an initial increase followed by a drastic drop in the resistance of the film at 257, 289, 421, 587 and 129 kΩ times and for pristine or non-radiated, 10, 20, 30 and 40 min, respectively, with a rise in the relative humidity level. It was also observed that under the effect of humidity, the capacitance of the DNA thin film increased to 935, 581, 1035, 301 and 329 nF times for the same corresponding exposure periods. The capacitive/resistive sensor was found to demonstrate a quasi-linear function with relative humidity in the range of 20-99.9% with only a small hysteresis and a response/recovery time of about 120 s. Generally, these humidity-dependent resistive and capacitive properties demonstrated in this current work may suggest utilization of Al/DNA/DNA Schottky diodes as a promising alternative for use in humidity meters.